Dynamic Fracture and Energy Evolution Characterization of Naturally Fractured Granite Subjected to Multilevel Cyclic Loads. (20th February 2021) - Guo, Ning; Li, Changhong; Liu, Hao; Wang, Yu
Abstract : Naturally fractured rock mass is susceptible to stress disturbance and could result in the stimulation of natural fractures and even serious geological hazards. In this work, multilevel uniaxial fatigue loading experiments were carried out to reveal the fracture and energy evolution of naturally fractured granite using stress-strain descriptions and energy evolution analysis. Results reveal the influence of natural fracture on mechanical properties of granite, regarding the fatigue lifetime, fatigue deformation characteristics, fatigue damage, energy evolution, and fatigue failure pattern. Volumetric and shear processes caused by the sliding and shearing along the natural fracture control the whole failure process. The energy dissipation and release characteristics are strongly impacted by natural fractures. The elastic energy and dissipated energy both decrease with increasing natural fracture volume, growth of the dissipated energy becomes faster for rock near to failure. It is proved that the dissipated energy is mainly used to activate the preexisting natural fractures.